Proceedings of International Electron Devices Meeting
DOI: 10.1109/iedm.1995.499239
|View full text |Cite
|
Sign up to set email alerts
|

Completely planarized W plugs using MnO/sub 2/ CMP

Abstract: In tungsten (W) polishing, MnO 2 has been used as an abrasive to form plugs without etching holes in seams during CMP. We found that MnO 2 polishes 1.5 times faster than the standard A1 2 O 3 abrasive, and can be completely removed during the cleaning process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[10][11][12] Polishing conditions were, pad: IC 1000 (Rodel Inc.); rotation speed: 30 rpm; pressure: 163 g/cm 2 ; pH of slurry, fumed silica: 10.4 and MnO 2 : 7.0. The removal rate was measured in unpatterned layers .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Polishing conditions were, pad: IC 1000 (Rodel Inc.); rotation speed: 30 rpm; pressure: 163 g/cm 2 ; pH of slurry, fumed silica: 10.4 and MnO 2 : 7.0. The removal rate was measured in unpatterned layers .…”
Section: Methodsmentioning
confidence: 99%
“…Polishing of these layers was performed by commercially available fumed silica slurry (SC-1, Cabot Inc.) and MnO 2 and Mn 2 O 3 slurries manufactured by Mitsui Metal and Smelting Co. Ltd., Japan. [10][11][12] Polishing conditions were, pad: IC 1000 (Rodel Inc.); rotation speed: 30 rpm; pressure: 163 g/cm 2 ; pH of slurry, fumed silica: 10.4 and MnO 2 : 7.0. The removal rate was measured in unpatterned layers .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] In our prior work, we demonstrated that MnO 2 slurry polishes W films without using an additional liquid oxidizer, and does not etch the seam of the plug during the CMP. 16) In this paper, we have studied the CMP mechanism using MnO 2 slurry from the thermodynamic and Mohs hardness points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Mn oxide particles have begun to attract attention for use as polishing particles. 18,19 The objective of this study was to use Mn-based oxide particles to prepare slurries for CMP of SiC substrates. The experimentally observed material removal rate and surface morphology were analyzed to determine the effects of pH and temperature of the Mn-based slurries on the SiC-CMP process characteristics.…”
mentioning
confidence: 99%